Apostle of persuasion: theology and rhetoric in the Pauline letters - Thompson, James W. (Baker Academic, a division of Baker Publishing Group, 2020)
This book is the culmination of a career of researching and teaching Paul's letters. Highly respected senior New Testament scholar James Thompson offers a unique approach to Pauline theology, focusing on Paul's attempts to persuade his audience toward moral formation. Thompson recognizes Paul as a pastor who brought together theology and rhetoric to encourage spiritual formation in his communities. Attempts to find total consistency in Paul's writings fail, says Thompson, because Paul's persuasive tactics changed depending on the situation he was addressing. --